The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/eurheartj/ehs072
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of aged bone marrow with young cells repopulates cardiac-resident bone marrow-derived progenitor cells and prevents cardiac dysfunction after a myocardial infarction

Abstract: Bone marrow reconstitution with young BM cells in aged recipients restored progenitors in both the BM and, most importantly, the myocardium. The number and function of cardiac-resident BM-derived progenitor cells in the aged myocardium prior to injury was the major determinant for successful recovery of cardiac function. The aged heart was rejuvenated with young BM cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…This data allows us to hypothesize that the bone marrow SSEA1+ cells may replenish the activated myocardial SSEA1 population. Previous reports have described the phenomenon of bone marrow cells contributing to the cardiac progenitor pool in the myocardium [7,36]. This is the first evidence that suggests a similar occurrence with SSEA1+ cells.…”
Section: Discussionsupporting
confidence: 63%
“…This data allows us to hypothesize that the bone marrow SSEA1+ cells may replenish the activated myocardial SSEA1 population. Previous reports have described the phenomenon of bone marrow cells contributing to the cardiac progenitor pool in the myocardium [7,36]. This is the first evidence that suggests a similar occurrence with SSEA1+ cells.…”
Section: Discussionsupporting
confidence: 63%
“…Old donors exhibit reduced tolerance to ischemia and decreased transplant survival within ischemic muscle[251]. Similarly, older recipients have a diminished therapeutic response to receiving stem cells from donors of any age[251,254]. To overcome these effects related to cellular senescence, many strategies are being developed as recently reviewed[257].…”
Section: Ex Vivo Genetic Optimization Of Stem Cellsmentioning
confidence: 99%
“…Recently, we evaluated the effect of cardiac‐resident BMSCs on the recovery of cardiac function after injury in aged animals . We found that BM reconstitution in old recipient mice with young donor cells improved cardiac functional recovery following injury.…”
Section: Introductionmentioning
confidence: 99%